Essentials of personnel assessment and selection - Guion, Robert M.; Highhouse, Scott (New York : Lawrence Erlbaum Associates, 2006)
(from the book) Essentials of Personnel Assessment and Selection distills and updates the "essentials" from Guion's best-selling 1997 book Assessment, Measurement, and Prediction for Personnel Decisions. This new textbook gives managers and students the nuts and bolts of assessment processes and selection techniques. It covers basic and advanced concepts in a straight-forward, readable style. The book is certainly appropriate for use as a text for advanced undergraduates and master's level students interested in becoming users of research-based assessment and selection information and techniques.
About the Authors
About This Book
Part I: Deciding What to Assess
Understanding Personnel Assessment
Analyzing Organizations and Jobs
Developing Predictive Hypotheses
Knowing What's Legal (and What's Not)
Part II: Knowing How to Assess
Minimizing Error in Measurement
Predicting Future Performance
Using Multivariate Statistics
Making Judgments and Decisions
Analyzing Bias and Assuring Fairness
Part III: Choosing the Right Method
Assessing Via Tests
Assessing Via Ratings
Assessing Via Inventories and Interviews
Combining Multiple Assessments
References
Author Index
Subject Index
str. 341-362: Bibliografija
str. 363-368: Autorsko kazalo
str. 369-379: Kazalo pojmova
Keywords: procjena zaposlenika; evaluacija zaposlenika